2005
DOI: 10.1097/01.mao.0000169778.54162.7d
|View full text |Cite
|
Sign up to set email alerts
|

Combined Retrosigmoid Retrolabyrinthine Vestibular Nerve Section: Results of our Experience over 10 Years

Abstract: VN performed using retrosigmoid-retrolabyrinthine approach has low complication and high vertigo control and hearing preservation rates. It can be applied as an initial surgery or reserved as the last step when the other surgical treatments have failed to control vertigo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…322 Retrospective cohort studies have demonstrated vertigo control rates that range from 78% to .90%. [330][331][332][333][334] Complications from this procedure include hearing loss, facial nerve injury, postoperative headache, and risks of craniotomy, such as bleeding, meningitis, and CSF leak. 317,322 Residual vestibular function resulting in persistent symptoms may result due to incomplete VNS, as there is not a well-defined separation between the vestibular and cochlear nerve.…”
Section: Supporting Textmentioning
confidence: 99%
See 1 more Smart Citation
“…322 Retrospective cohort studies have demonstrated vertigo control rates that range from 78% to .90%. [330][331][332][333][334] Complications from this procedure include hearing loss, facial nerve injury, postoperative headache, and risks of craniotomy, such as bleeding, meningitis, and CSF leak. 317,322 Residual vestibular function resulting in persistent symptoms may result due to incomplete VNS, as there is not a well-defined separation between the vestibular and cochlear nerve.…”
Section: Supporting Textmentioning
confidence: 99%
“…VNS is not specifically classified as an inner ear ablative procedure; rather, it is an intradural procedure that involves selective transection of the vestibular nerve while preserving the cochlear nerve 322 . Retrospective cohort studies have demonstrated vertigo control rates that range from 78% to >90% 330–334 . Complications from this procedure include hearing loss, facial nerve injury, postoperative headache, and risks of craniotomy, such as bleeding, meningitis, and CSF leak 317 , 322 .…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
“…Total labyrinthectomy is performed in patients with poor hearing and has reported success rates of approximately 95%. [1][2][3] In MD, these procedures provide a stabilized vestibular system by eliminating fluctuating vestibular signals. However, these 2 operations cause unilateral inner ear dysfunctions in patients, therefore having negative effects on the vestibulo-ocular reflex (VOR) and global balance.…”
Section: Introductionmentioning
confidence: 99%
“…Vestibular input to the CNS is normally bilateral and symmetrical. 12,25,34 Symptoms of vertigo typically develop when vestibular disease on 1 side causes this input to become asymmetrical. The rationale for ablating the peripheral vestibular system, therefore, is to completely eliminate the abnormal vestibular input from the diseased side.…”
Section: Discussionmentioning
confidence: 99%
“…This should allow for near complete resolution of a patient's vestibular symptoms in Ménière disease. 12,34 In the 1930s, McKenzie and Dandy 16 introduced the concept of sectioning only the vestibular portion of cranial nerve VIII via a suboccipital craniectomy to treat symptoms of intractable vertigo in patients with medically refractory Ménière disease. In 1961, House 13 described the middle cranial fossa approach to the IAC for vestibular nerve sectioning.…”
Section: Discussionmentioning
confidence: 99%